THE EFFECT OF TIME AVAILABILITY, SOCIAL PRESENCE, AND EMOTIONAL CONDITION ON IMPULSE BUYING BEHAVIOR AT SOCIOLLA STORE MANADO TOWN SQUARE - Sanger, Keren; Pandowo, Merinda H. Ch.; Rumokoy, Lawren Julio (Universitas Sam Ratulangi, 2024)
This study aims to examine the effect of time availability, social presence, and emotional condition on impulsive buying behavior. This research is descriptive quantitative research. Quantitative method is research system which is systematically, detailed, and planned clearly from the planning up to the research design (Sugiyono, 2016). In this study, the unit of analysis to be studied is an individual, namely respondents who have shopped at Sociolla Store Manado Town Square. Data analysis technique in this research is Partially Least Square (PLS). The result of this research shows that the magnitude of the effect of the time availability variable on emotional condition is positive 0.163 or 16.3%, which means that the availability of time has a positive effect on emotional condition by 16.3% in this study. From the magnitude of the social presence variables on emotional condition is 0.272 or 27.2%, which means that the social presence has a positive influence on emotional condition by 27.2% in this study. the effect of emotional condition on impulsive buying behavior, the P value is 0.018, which is smaller than the upper limit of 0.05 so that this hypothesis can be said to be significant. Keyword: Impulse Buying Behavior, Time Availability, Social Presence, Emotional Condition